Social Media As A Tool Of Sexual Transactions Of Men Who Have Sex With Men (MSM) In Buleleng Regency Bali - Putu Sukma Megaputri; Made Bayu Oka Widiarta; Putu Indrawan (Alma Ata University Press, 2020)
Men who have sex with men (MSM) is the community that has become the largest epicenter in the transmission of HIV / AIDS. At present the MSM community is a marginalized community, so it is difficult to observe its development, this is because of the negative stigma from the community environment towards MSM. So they use social media in forming communities and offering sexual relations. The aim of study was to analyze the social media that were most often used by MSM in sexual transactions activity. A cross sectional approach was applied in this study with a sample of 58 people, selected by snowball and using a questionnaire to collect quantitative data. Respondent characteristics data were analyzed descriptively, then bivariate analysis to determine the relationship of independent variables with dependent variables and independent variables that could be included in multivariate analysis. Multivariate analysis with logistic regression was used to determine the effect of independent variables on sexual transactions conducted by MSM. The results found that, Grindr social media is the most dominant among Whatsapp, Facebook, Me Chat and other social media. Meanwhile, based on the technique of having sex, sex activeness is seen in MSM who have anal and oral relations. It was also reported in the results of research that getting younger MSM increasingly increases sexual desire. The conclusions of this study are MSM who use Grindr, with anal and oral sex techniques as well as young age, which increases sexual activity.